2020
DOI: 10.1109/ojits.2020.3027518
|View full text |Cite
|
Sign up to set email alerts
|

Optimised Traffic Light Management Through Reinforcement Learning: Traffic State Agnostic Agent vs. Holistic Agent With Current V2I Traffic State Knowledge

Abstract: Traffic light control falls into two main categories: Agnostic systems that do not exploit knowledge of the current traffic state, e.g., the positions and velocities of vehicles approaching intersections, and holistic systems that exploit knowledge of the current traffic state. Emerging fifth generation (5G) wireless networks enable Vehicle-to-Infrastructure (V2I) communication to reliably and quickly collect the current traffic state. However, to the best of our knowledge, the optimized traffic light manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Complementary to the aforementioned study [113] where TLC with varying portions of V2I enabled vehicles ranging from 0 to 100% at a single intersection, the authors of [114] examined the performance impact of traffic state information collected via V2I communication for road networks consisting of multiple intersections considering the extreme cases of 0% of V2I enabled vehicles in [113] (equivalent to their agnostic agent) and 100% of V2I enabled vehicles in [113] (equivalent to their holistic agent). The study's key contribution is a detailed comparison of a representative state-of-the-art agnostic DRL agent that is unaware of the current traffic state versus a representative state-of-the-art holistic DRL agent that is aware of the current traffic state.…”
Section: Traffic Light Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary to the aforementioned study [113] where TLC with varying portions of V2I enabled vehicles ranging from 0 to 100% at a single intersection, the authors of [114] examined the performance impact of traffic state information collected via V2I communication for road networks consisting of multiple intersections considering the extreme cases of 0% of V2I enabled vehicles in [113] (equivalent to their agnostic agent) and 100% of V2I enabled vehicles in [113] (equivalent to their holistic agent). The study's key contribution is a detailed comparison of a representative state-of-the-art agnostic DRL agent that is unaware of the current traffic state versus a representative state-of-the-art holistic DRL agent that is aware of the current traffic state.…”
Section: Traffic Light Controlmentioning
confidence: 99%
“…They also compared a reward function that considers only the average vehicle velocity with a composite reward function that takes into account a weighted combination of the average vehicle velocity, vehicle flow rate, CO 2 emissions, and driver stress level. They found that the holistic system substantially [114].…”
Section: Traffic Light Controlmentioning
confidence: 99%
“…Sparse reward settings are one of the obstacles for reinforcement learning [16]. That is, where the agent receives a reward only when meeting the target level.…”
Section: Figure 1: Reinforcement Learning Agent-environment Cyclementioning
confidence: 99%
“…The implementation of RL have been studied extensively to find the optimal traffic signal timing policy since the 1990s [1,5,16]. Earlier work was limited to Tabular Q-learning in RL.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation